Sustainability of soil health and system productivity through arecanut based cropping system in the NE Region of India - Paul, S.C.; Acharya, G.C.; Chakraborty, R.; Maheswarappa, H.P.; Hussain, M.; Ray, A.K. (Journal of Plantation Crops, 2020)
The North-Eastern part of India contains seven states out of which, Assam is the major producer of arecanut. An attempt was made to study the impact of arecanut based multiple cropping system with proper utilization of recyclable resources on the long-term sustainability of acid soil at Kahikuchi. A long term arecanut based High-Density Multispecies Cropping System garden comprised of two models viz., Model-1 (M1): arecanut (Areca catechu), black pepper (Piper nigrum), banana (Musa spp.), citrus (Citrus limon) and clove (Syzygium aromaticum) and Model-2 (M2): arecanut, black pepper, banana, citrus and nutmeg (Myristica fragrans) as component crops was used. Both the models were sub-divided into three treatments viz., Full dose of recommended fertiliser (T1), 2/3rd of the recommended dose (T2) and 1/3rd of the recommended dose (T3) combined with treatment-wise recycling available biomass in the form of vermicompost and each treatment was replicated thrice. The results indicated that the quantity of recyclable biomass generated ranged between 8.27 to 12.23 t ha-1 year-1 and 8.11 to 12.38 t ha-1 year-1 in model-1 and model-2, respectively and revealed that the T2 treatment in both models improved the soil properties with respect to soil pH, organic carbon, available N, P and K status. Economics of the cropping system revealed that the maximum return was obtained from both Models under T2. The average benefit:cost ratio of T1, T2 & T3 was 3.38, 4.42 & 3.47 under model-1 and 3.34, 4.08 and 3.40 under model-2, respectively. Sustenance of soil pH above 5.0 over the years in the arecanut rhizosphere in both the models were found under T2, but T1 and T3 treatments showed a slow declining of pH towards increasing soil acidity.